Diabetes Medication Education and Diabetes Medication Adherence in Indonesia in 2023: Indonesia Health Survey (Survei Kesehatan Indonesia) - Fatmawati, Putri; Afiyah, Siti Nur (Hypertension Prevention and Control Research Center, The Polytechnic of Health of Banten, 2024)
Diabetes Mellitus (DM) is one of the metabolic diseases that is among the four leading causes of death in Indonesia. Uncontrolled blood glucose levels in diabetes mellitus patients can lead to serious complications. One effort to prevent complications of diabetes mellitus is to enhance adherence to optimize medication programs. The objective of this study is to provide an overview of diabetes patients who receive education related to diabetes medication and adherence to diabetes medication in Indonesia, as well as to determine the relationship between receiving diabetes medication education and medication adherence among diabetes patients in Indonesia. The data used in this study is from the 2023 Indonesian Health Survey (SKI), which includes data on respondents who received diabetes medication education and data on medication adherence in 38 provinces in Indonesia. The analytical method employed is logistic regression, analyzed on RStudio version 4.4.0. Medication adherence is categorized into two binary categories: provinces with higher adherence and provinces with lower adherence, with the categorization threshold using the mean of medication adherence data. The frequency distribution results show 21 provinces with adherence above the mean and 17 provinces below the mean. The logistic regression results showed the estimated log odds of medication adherence was -15.67, the estimate for receiving diabetes medication education was 0.1907, with adjusted odds ratio 1.21, and p-value <0.001, indicating that, compared to an alpha value of 0.05, diabetes medication education is significantly related to medication adherence among diabetes patients in Indonesia.